Increased ultrasonographic endometrial thickness is associated with poor survival in patients with endometrial cancer: An Israel gynecologic oncology group study. Issue 5 (May 2021) - Namazov, Ahmet; Gemer, Ofer; Hag-Yahia, Nasreen; Eitan, Ram; Raban, Oded; Vaknin, Zvi; Leytes, Sophia; Lavie, Ofer; Ben-Arie, Alon; Amit, Amnon; Levy, Tally; Volodarsky, Michael; et al.
Abstract: Background: We aimed to assess the association of pre-operatively evaluated ultrasonographic endometrial thickness with outcomes of patients with endometrial cancer. Methods: An Israel Gynecologic Oncology Group multicenter retrospective cohort study of consecutive patients with endometrial cancer who underwent surgery between 2002 and 2014 in one of eleven academic centers. Patients were categorized by endometrial thickness into two groups: ≤20 mm and >20 mm. Clinical and pathological features were compared using Student T-test for continuous variables and Chi-square or Fisher's exact test for categorical variables. Survival measures were plotted with the Kaplan-Meier method and compared using the log-rank test. A Cox proportional hazards model was used for multivariable comparison of associations. Results: 1113 patients in whom endometrial thickness data was recorded were the subject of this study and included 2 groups: ≤20 mm (n = 930), >20 mm (n = 183). The median follow-up was 52 months (range 12–120 months). Patients with endometrial thickness >20 mm had significantly lower recurrence-free survival (log rank, p < .0001), disease-specific survival (log rank, p = .01), and overall survival (log rank, p < .0001). On multivariate Cox proportional hazards analysis, endometrial thickness >20 mm remained independently associated with an increased hazard of recurrence and death (HR = 1.77, 95% CI 1.07–2.96, p = .03 for recurrence; and HR = 1.68; 95% CI 1.07–2.65; p = .03 for overall survival). Conclusion: In patients with endometrial cancer, endometrial thickness>20 mm as measured preoperatively by ultrasound, is independently associated with decreased recurrence-free and overall survival. This finding suggests that thick endometrium may be considered as one of the risk factors for poor prognosis.